The Environmental Variable in the Core-Periphery Relational Axis According to the World-System Theoretical Perspective. an Analysis on Latin American Roles in Its Relation with the Core of the World-Systems2 [la Variable Ambiental en el Eje Relacional Centro-Periferia Según la Perspectiva Teórica Análisis de Sistema-Mundo. Un Análisis en Los Roles de América Latina en Su Relación Con Los Países Centrales del Sistema Mundial] - Vasquez-Bustamante, J (Editora PUC-Minas, 2019)
This article aims to add the Environmental Crisis as a variable in the core-periphery relational axis according to the theoretical perspective of the World-Systems Analysis in the search of identifying potential changes in its flows and in Latin American roles as a peripheral region. Throughout a literature review, the main references of the World-Systems Analysis theoretical perspective regarding the Environmental Crisis phenomenon are searched for; the main defining aspects of the core-periphery relational axis according to the World-System Analysis are identified and described; some effects and consequences of the Environmental Crisis - which are lay out by Latin-American intellectuals linked to the ECLAC - that are potential change factors between core and periphery are set out: in addition, a relation between those change factors and determined elements and problematic precedents of the Ecuadorian Yasuní ITT Initiative -a global environmental proposal- is offered. © 2019 Editora PUC-Minas. All rights reserved.